Prevalence of depression & assessment of risk factors among school going adolescents - Vashisht, Arun; Gadi, Nabeel Ahmed; Singh, Jagjeet; Mukherjee, Moushumi P; Pathak, Rambha; Mishra, Prabhaker (Indian Journal of Community Health, 2014)
Background: Adolescents comprise nearly one-fifth of the total population of India. Undiagnosed adolescent depression can have potentially long term serious consequences along with increased risk of suicide. Objectives: To find out the prevalence of depression among school going adolescents and the socio environmental risk factors associated with it. Materials and Methods: A cross sectional study was carried out among 1632 school going adolescents (13-19yrs) in the rural and urban areas of district Ambala. Two pretested questionnaires were used. Depression subscale of Symptom Check List 80 (SCL 80) was used for ascertaining the prevalence of depression and a self-report questionnaire to assess effect of socio-environmental factors. Results: 29.9% adolescents had evidence of depression having cut off score > 13 in depression subscale of SCL 80. Most of the students in depression syndrome group were found to be suffering from mild category 22.9% followed by moderate category 7%. Depression was found to be associated with increasing age, low socio economic status and urban students. Conclusion: Regular screening of adolescents for depression and strengthening of school health services could provide the impetus for detection, prevention & management of adolescent depression.